ความไม่มั่นคงด้านพลังงานของเมียนมาร์: ที่มา พลวัต และแนวโน้ม - ปานหทัย วาสนาวิจิตร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
The objective of this thesis is to analyze the energy insecurity of Myanmar by using the concept of ‘Energy Security’ to determine index on the issues of Myanmar’s energy security in 2010 - 2015. The time period under study focuses on the Myanmar government led by President Thein Sein who emphasized energy policies in parallel with the investment policies of the country. The policies resulted in a surge of foreign direct investment into Myanmar, particularly in energy infrastructure, such as natural gas, oil, hydropower, and coal. The results of the analysis of Myanmar s energy security are based on the index of energy security in four areas, namely availability, accessibility, affordability and acceptability. The findings suggest that foreign direct investment in energy from 2010 to 2015 did not lead to the development of Myanmar s energy sector because Myanmar s energy sector became less stable and reliable. This was reflected in energy production that was not available for domestic demand, energy infrastructure or energy networks that were not extensive, while there was a lack of transparency and unacceptable management of the energy sector. These results broadly reflect the dynamics of energy insecurity in Myanmar.